Barriers to reporting medical errors from the perspective of obstetric residents: A qualitative study - Reza Ghaffari; Roghaiyeh Nourizadeh; Khadijeh Hajizadeh; Maryam Vaezi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Patient safety is one of the basic dimensions of quality of care. Medical errors are one of the most important and influential factors in the quality of care and clinical outcomes, which can have a significant economic effect. The aim of this study was to explore barriers to reporting medical errors from the perspective of obstetric residents. MATERIALS AND METHODS: This was a qualitative study using a conventional content analysis approach. Data collection was performed through 18 semi-structured and in-depth individual interviews and a group discussion session with 13 obstetricians in Tabriz, Iran. Purposeful sampling started in December 2021 and continued until data saturation in October 2022. Findings were analyzed concurrently with data collection using MAXQDA 10 software. RESULTS: Four categories were obtained after analysis of the data: individual and organizational factors, the nature of the error, the educational hierarchy, and the fear of reactions and consequences of error reporting. CONCLUSION: Considering the importance of patient safety, it is necessary to improve the quality of education and awareness of residents and direct supervision of attending, emphasize promoting professional communication and changing educational policies and strategies to reduce errors, and remove barriers to error reporting. Instead of blaming those in error, the organizational culture should support error reporting and reform the error-prone system, through which positive results will be achieved for both patients and healthcare providers.